2022
DOI: 10.3390/children9020270
|View full text |Cite
|
Sign up to set email alerts
|

Alberta Infant Motor Scale (AIMS) Performance of Early-Term Greek Infants: The Impact of Shorter Gestation on Gross Motor Development among “Term-Born” Infants

Abstract: Early-term birth (37+0 to 38+6 gestational weeks) may have a negative impact on infants’ neurodevelopment compared to delivery at 39 weeks or beyond. The purpose of this study was to evaluate the gross motor development of early-term infants using the Alberta Infant Motor Scale (AIMS). A total of 1087 healthy infants (559 early-term and 528 full-term infants born at 39+0 to 41+6 weeks of gestation) were studied. Mean AIMS scores were compared between the two groups at monthly intervals. The impact of gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Three studies examining the association between growth-related variables and FMS, of which one was rated as having high methodological quality, found no association in children aged <1 year (de Paiva et al, 2010;Jensen et al, 2019;Syrengelas et al, 2022), one study found a positive association (Siziba et al, 2018), and one study found a negative association (Nahar et al, 2019). Both studies examining the association between growth-related variables and FMS in children aged 1-2 years found no association (Ribe et al, 2018;.…”
Section: Correlates Of Early Childhood Motor Skillsmentioning
confidence: 97%
See 2 more Smart Citations
“…Three studies examining the association between growth-related variables and FMS, of which one was rated as having high methodological quality, found no association in children aged <1 year (de Paiva et al, 2010;Jensen et al, 2019;Syrengelas et al, 2022), one study found a positive association (Siziba et al, 2018), and one study found a negative association (Nahar et al, 2019). Both studies examining the association between growth-related variables and FMS in children aged 1-2 years found no association (Ribe et al, 2018;.…”
Section: Correlates Of Early Childhood Motor Skillsmentioning
confidence: 97%
“…In children aged <1 year, five studies, of which one study was rated as having high methodological quality, found a positive association between age and FMS (Makela et al, 2018;Piallini et al, 2016;Righetto Greco et al, 2019;Siziba et al, 2018;Syrengelas et al, 2022), and two studies found no association (Majnemer & Barr, 2005;Nahar et al, 2019). In children aged 1-2 years, one study rated as having high methodological quality found a positive association between age and FMS (Costa et al, 2021), and one study found a negative association .…”
Section: Correlates Of Early Childhood Motor Skillsmentioning
confidence: 97%
See 1 more Smart Citation
“…The AIMS positional scores and total scores have been used to compare motor development between preterm and full-term infants, including their reliability [13]. As infants motor development features could vary, how well they did each item should be checked for an accurate AIMS measurement and evaluation [14]. Weight-bearing, posture, and antigravity movement are key descriptors of motor skills used in the AIMS.…”
Section: Introductionmentioning
confidence: 99%